Concomitant body-wide trauma patterns in patients with head and neck injuries: a comparison based on the trauma register DGU® by the German trauma society and the dortmund maxillofacial trauma registry - Ákos Bicsák; Fatma Topcuoglu; Stefan Hassfeld; Rolf Lefering; Lars Bonitz; Jens-Peter Stahl (European Journal of Medical Research, 2025)
Abstract Introduction Interdisciplinary trauma patients with multiple injuries require special attention from the first minute of care. This study aimed to determine the overall injury distribution in patients with head and neck injury (HNI) with respect to the head and neck injury location. Methods Data on patients with HNI were collected in the Dortmund Maxillofacial Trauma Register 2007–2017 based on a review of patient radiographs and files. All patients with concomitant injuries to central body parts were selected and analysed further by an expert traumatologist collecting data on GCS, ISS, injuries and outcome. Further comparisons with data from the German TraumaRegister DGU® 2007–2022 were acquired and used to determine whether the patient group with head and neck injuries differed from other injured patients. Results A total of 70.212 patients with head and neck injuries were identified from the 344.754 reported cases in the TraumaRegister DGU®. Among the 344,754 patients, 6127 were registered with mandibular injuries (1.8% of the total population/8.7% of patients with HNI), panfacial injuries were reported in 10,001 patients (2.9%/14.2%), and midfacial injuries were reported in 42,045 patients (12.2%/59.9%). Injuries to the thorax (39.5% of non-HNI patients vs. 35.4% of HNI patients), abdomen (10.8% vs. 6.7% of HNI patients), and extremities (25.6% non-HNI vs. 20.1% HNI, respectively), spine (29.8% non-HNI patients vs. 27.0% HNI patients), lower extremities (26.1% vs. 22.3%, respectively), and iliac bone (16.5% non-HNI patients vs. 13.6% HNI patients) and upper extremities (29.0% non-HNI patients and 33.8% HNI patients). A total of 289 severely injured patients from 7010 head and neck injuries were selected from the Dortmund Maxillofacial Trauma Register. The mechanism of the injuries included falls (n = 143; 49.5%), road traffic accidents (75, 26.0%), interpersonal violence (48, 16.6%), work-related accidents (14, 4.8%), sports accidents (7, 2.4%) and other causes (2, 0.7%). No in-hospital deaths were reported in this population. Seven of the 289 patients (2.4%) needed reanimation upon arrival at the emergency room. In this group, the average ISS = 50.3 (Injury Severity Score), and the GCS = 7.1 (Glasgow Coma Scale). Six of the 7 patients had a calvarial fracture (86%), and injuries to the cervical, thoracic and lumbar spine were detected in 1, 2 and 2 patients (14%, 28% and 28%, respectively). Ventilation was applied in 4 patients (57%). Overall, most soft tissue injuries were identified in the face (128) and head areas (57), followed by the thorax and back areas (54 and 28). The most joint injuries were found in the hip, shoulder and radiocarpal and hand regions (11, 10 and 10 injuries, respectively). Most cases were considered severe. The body-wide fracture distribution was similar: most fractures occurred in the calvaria (227) or thoracic area (27 multiple rib fractures and 15 single rib fractures). Similarly, the rates of fractures in the thoracic spine (15), lumbar spine (11) and pelvic bone (9) were high. The 289 analysed patients accounted for 4.1% of all patients with head and neck injuries. Together with the 2.47% of patients with CSI (cervical spine injury), all HNI patients with any central body injury accounted for nearly 6.5% of all HNI patients. The results are presented in heatmaps. Conclusions Patients with HNI tend to have slightly different injury pattern in the whole body than non-HNI patients. Head and neck injuries in different locations show different patterns of concomitant injuries. Panfacial fractures, forehead and lateral and central midfacial injuries combine with spine injuries, central midface, mandibular and dentoalveolar injuries were not observed with hip fracture. Injuries to the thorax were not diagnosed in case of dentoalveolar injuries.